2019
DOI: 10.33119/erfin.2019.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Forward Guidance Matter in Small Open Economies? Examples from Europe

Abstract: The effect of forward guidance on interest rate expectations in small, open economies is often described as heterogeneous. There are examples when financial markets adjusted term structure to reflect interest rate forecasts provided in the projections published by the central banks. On the other hand, medium-term expectations can persistently deviate from trajectories presented by decision-makers, influenced by foreign monetary policy. Our aim is to find the maximal forecast horizon where the domestic forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Measuring the impact of forward guidance policy in the sample of European small open economies, Rybacki (2019) found only limited evidence that domestic forward guidance policies permanently signal the expected changes in market interest rates during the period between 2007 and 2018. However, examining the period after 2012-when financial markets began to pay more attention to the communication of central banks-Rybacki found that the expectations about interest rates were more affected by ECB policy than by domestic forward guidance when the forecast horizon is longer than four quarters.…”
Section: The Extensive Effects Of Ump and Qementioning
confidence: 99%
“…Measuring the impact of forward guidance policy in the sample of European small open economies, Rybacki (2019) found only limited evidence that domestic forward guidance policies permanently signal the expected changes in market interest rates during the period between 2007 and 2018. However, examining the period after 2012-when financial markets began to pay more attention to the communication of central banks-Rybacki found that the expectations about interest rates were more affected by ECB policy than by domestic forward guidance when the forecast horizon is longer than four quarters.…”
Section: The Extensive Effects Of Ump and Qementioning
confidence: 99%